Regulatory Framework of Reusable Packaging Systems for Sustainable Circular Economy in Indonesia - Nadila Putri Shenindita; Andi Nostadi (Yayasan Cerdas Pedia Indonesia, 2026)
This study examines the effectiveness of Extended Producer Responsibility regulations in Indonesia through an empirical socio-legal analysis of the Alner digital platform. Despite statutory mandates requiring waste reduction, enforcement remains weak due to a structural gap between international standards and domestic legal realities. Utilizing Lawrence Friedman’s legal system theory, this research demonstrates how Alner’s digital tracking technology functions as a shadow legal structure. By transforming environmental investments into authentic legal evidence, Alner bridges the enforcement vacuum, enabling producers to verify statutory compliance under Ministry of Environment and Forestry Regulation P.75/2019. Operational data from 150,000 reuse cycles proves that technology-driven private governance can successfully engineer legal behavior toward a sustainable circular economy. Ultimately, this study recommends that the Indonesian government deeply integrate these digital verification standards into its national oversight systems to better guarantee the constitutional human right to a healthy environment and strongly foster accountable digital environmental governance practices worldwide.